2013
DOI: 10.1152/ajpendo.00602.2012
|View full text |Cite
|
Sign up to set email alerts
|

Role of androgen and vitamin D receptors in endothelial cells from benign and malignant human prostate

Abstract: Forty years ago, Judah Folkman (Folkman. N Engl J Med 285: 1182-1186, 1971 proposed that tumor growth might be controlled by limiting formation of new blood vessels (angiogenesis) needed to supply a growing tumor with oxygen and nutrients. To this end, numerous "antiangiogenic" agents have been developed and tested for therapeutic efficacy in cancer patients, including prostate cancer (CaP) patients, with limited success. Despite the lack of clinical efficacy of lead antiangiogenic therapeutics in CaP patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 107 publications
1
5
0
Order By: Relevance
“…Indeed, and in agreement with the results herein, our research group has previously reported that not only VEGF but also AR expression was significantly decreased following nintedanib administration to TRAMP mice during earlier time intervals in relation to those in the present study . Furthermore, it is well known that endogenous AR expression is important for regulating tumor cell differentiation and proliferative status and that the maintenance of this receptor function is a critical factor for prostate cancer development and progression . Finally, considering the aforementioned data, we speculate that negative interferences on VEGF‐mediated pro‐angiogenic signaling in the prostate, such as nintedanib administration, can lead to simultaneous reduction in AR expression, thus indicating one of the mechanisms whereby this anti‐angiogenic agent slows tumor progression in TRAMP mice.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, and in agreement with the results herein, our research group has previously reported that not only VEGF but also AR expression was significantly decreased following nintedanib administration to TRAMP mice during earlier time intervals in relation to those in the present study . Furthermore, it is well known that endogenous AR expression is important for regulating tumor cell differentiation and proliferative status and that the maintenance of this receptor function is a critical factor for prostate cancer development and progression . Finally, considering the aforementioned data, we speculate that negative interferences on VEGF‐mediated pro‐angiogenic signaling in the prostate, such as nintedanib administration, can lead to simultaneous reduction in AR expression, thus indicating one of the mechanisms whereby this anti‐angiogenic agent slows tumor progression in TRAMP mice.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, binding of VEGF to its receptors on endothelial cells promotes and enhances vascular permeability and facilitates angiogenesis and revascularization [ 40 ]. More interestingly, Godoy et al [ 57 ] linked androgens to the upregulation of VEGF and mitotic cyclins, which are known to increase EPC proliferation [ 57 ]. In clinical studies it was demonstrated that flow-mediated dilation (FMD) is reduced in patients with TD and is enhanced in response to testosterone therapy [ 23 , 58 - 60 ].…”
Section: Androgen Modulation Of Endothelial Function In Erectile Physmentioning
confidence: 99%
“…The improved understanding of prostate cancer biology in recent years led to the development of drugs directed against precise tumorigenesis-associated molecular pathways [ 2 ]. Angiogenesis, the development of new blood vessels, is recognized as one of the hallmarks of malignancy and prostate vasculature has been shown to play an important role in regulating the size and function of prostate malignancies [ 3 , 4 ]. Accordingly, several anti-angiogenic drugs have been tested in phase II and III trials in prostate cancer patients [ 5 ], including the oral non-selective tyrosine kinase inhibitors Sunitinib and Sorafenib.…”
Section: Introductionmentioning
confidence: 99%